2010
DOI: 10.1002/ejsp.706
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effect of social comparison on academic performance

Abstract: The present study was part of a large-scale cohort study among several thousand students in the Netherlands. The purpose of the study was to investigate the long-term effects of comparison choice, i.e., comparison with a target performing better or worse than oneself, and academic comparative evaluation, i.e., the extent to which one thinks one's performance is better or worse than that of others, on scores on standardized tests for reading comprehension and mathematics. While controlling for earlier performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…We have the same concerns as Wehrens et al (2010) in that the relationship between social comparisons and academic achievement, or in our case confidence, may not be causal in nature. Although it intuitively seems likely that a causal relationship is likely to exist, the data are correlational.…”
Section: Causality Concernsmentioning
confidence: 78%
See 2 more Smart Citations
“…We have the same concerns as Wehrens et al (2010) in that the relationship between social comparisons and academic achievement, or in our case confidence, may not be causal in nature. Although it intuitively seems likely that a causal relationship is likely to exist, the data are correlational.…”
Section: Causality Concernsmentioning
confidence: 78%
“…Blanton et al proposed that seeing a competent person can provide information on how to improve one's own performance. This was echoed in the study by Wehrens et al (2010), who argued that for upwards social comparisons to be motivating the higher level of performance has to seem attainable, and that requires a degree of self-confidence.…”
Section: Social Comparison and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, these comparisons can lead to direct coping through improved performance in the domain of comparison (e.g. Marx & Roman, 2002; Seta, 1982; Wehrens, Kuyper, Dijkstra, Buunk, & Van Der Werf, 2010). For instance, Blanton, Buunk, Gibbons, and Kuyper (1999) found that students who compared themselves to higher‐ versus lower‐performing classmates subsequently improved in the same academic domain.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…High school environments can have a strong social impact on students, largely because of time spent on campus, the impressionable age of students, and the desire to conform to peer norms and pressures. Because comparisons and rankings are commonplace in many school systems and often linked to rewards and accommodations, making social comparisons may become engrained within students and transcend the high school years 42,43 . While many schools adopt ranking systems based on academic performance, evidence shows influences external to merit alone factor into teacher and administrative rankings such as perceived popularity and sport performance, 44 which may exacerbate social comparisons and competition.…”
Section: Discussionmentioning
confidence: 99%